Pharmacognostic prospection and physical and chemical characterization of A. esculentos fruits (Research, Society and Development, 2020)
The Abelmoschus esculentus (okra) belonging to the Malvaceae family, is a plant native to Africa and India and is part of the diet in various parts of the world. The fruits have carotene, folic acid, vitamin B1, B2, B3, Vitamin C, ethanedioic acid and amino acids. There are several therapeutic and nutritional properties attributed to okra. Thus, the objective of the present study was to carry out a pharmacognostic prospecting and to carry out the physico-chemical characterization of A. Esculentos fruits. The study was carried out with the fruits of A.esculentos collected in the city of Coelho Neto, Maranhão, The exsiccata was made and deposited in the Herbarium of the Federal University of Piauí Graziela Barroso (TEPB), afterwards the crude extract was obtained, subsequently pharmacognostic and photochemical analyzes were carried out and, finally, infrared analysis. The results show that samples are constituted by hydrolyzable tannins also flavonoids, from the group of flavonols and dihydroflavonoids in addition to cardiotonic glycosides, which are biologically active substances of pharmacological interest. Through infrared spectroscopy of the raw extract of Abelmoschus esculentus, physical-chemical, nutritional and functional characteristics were demonstrated. Therefore, the results presented in this initial study suggest that Abelmoschus esculentus is a species with great potential for further studies and future pharmacological application.